Corporate Governance in Jordan and Boardroom Diversity: A Critical Review of Literature - Mkheimer, Ibrahim Mohammad (European Scientific Journal, ESJ, 2018)
This paper focuses on critically analyzing the present literature which discusses the Corporate Governance (CG) concept in Jordan and board diversity, and the potential benefits obtained from adopting this concept in different streams like its impact on the total organizational performance. The paper also aims to present related theories and empirical literature focused on the composition of corporates’ boardroom and the role of its diversity in achieving their objectives such as competitive advantage. It also aims to determine the gaps and guidance for future studies. The review shows examples of basic theories, definition, methodologies, and certain industries deficiencies in previous studies and literature which limits the generalizability of their findings in specific environment, industry, and population. Finally, the study also presents implications on implementation, theory, and the best practice of Corporate Governance.